2020
DOI: 10.3390/cancers12030542
|View full text |Cite
|
Sign up to set email alerts
|

CITK Loss Inhibits Growth of Group 3 and Group 4 Medulloblastoma Cells and Sensitizes Them to DNA-Damaging Agents

Abstract: Medulloblastoma (MB) is the most common malignant brain tumor in children, and it is classified into four biological subgroups: WNT, Sonic Hedgehog (SHH), Group 3 and Group 4. The current treatment is surgery, followed by irradiation and chemotherapy. Unfortunately, these therapies are only partially effective. Citron kinase protein (CITK) has been proposed as a promising target for SHH MB, whose inactivation leads to DNA damage and apoptosis. D283 and D341 cell lines (Group 3/Group 4 MB) were silenced with es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 60 publications
0
35
0
Order By: Relevance
“…Previous studies have found that p27 acts as a tumor suppressor by closely binding to CIT to prevent its interaction with its activator RhoA, thereby regulating cytokinesis ( Serres et al, 2012 ). Recently, a study has found that inactivation of CIT significantly reduces RAD51, a factor that helps to repair DNA damage, thus causing accumulation of DNA damage in medulloblastoma cells and finally leading to apoptosis ( Pallavicini et al, 2020 ). In the current study, the microarray results revealed several key regulators that may be controlled by CIT.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that p27 acts as a tumor suppressor by closely binding to CIT to prevent its interaction with its activator RhoA, thereby regulating cytokinesis ( Serres et al, 2012 ). Recently, a study has found that inactivation of CIT significantly reduces RAD51, a factor that helps to repair DNA damage, thus causing accumulation of DNA damage in medulloblastoma cells and finally leading to apoptosis ( Pallavicini et al, 2020 ). In the current study, the microarray results revealed several key regulators that may be controlled by CIT.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that CITK could be a potential target for medulloblastoma treatment [ 128 , 129 ]. CITK knockdown by RNAi in SHH, Group 3 and 4 medulloblastoma cell lines impairs proliferation, induces cytokinesis failure, cell cycle arrest, and apoptosis via TP53-dependent and TP53 independent mechanisms [ 128 130 ].…”
Section: Microtubule Targeting Agents (Mtas) In Brain Tumorsmentioning
confidence: 99%
“…Moreover, all CITK-depleted cell lines show an accumulation of DNA damage, consistent with data obtained in neural progenitors of null mice [ 49 ]. Interestingly, these cells show also reduced level of the DNA-repair protein RAD51 and impairment of homologous recombination [ 129 ]. Lastly, CITK knockdown in MB cells potentiates the effect of radiation and cisplatin treatment [ 129 ].…”
Section: Microtubule Targeting Agents (Mtas) In Brain Tumorsmentioning
confidence: 99%
“…CIT functions in spindle orientation and during late cytokinesis [300][301][302][303]. CIT overexpression has been associated with cancers of various origin [304][305][306][307][308][309][310], likely through its kinase function that is, however, lost during chromosomal rearrangement in the FGFR2-CIT fusion (Figure 1). Transgenic mice expressing CIT variant lacking the kinase domain show defects in neurogenesis and spermatogenesis [311,312], due to aberrant cytokinesis that is followed by massive apoptosis.…”
Section: Fgfr2-citmentioning
confidence: 99%